LEITURA E CIVILIDADE: um estudo discursivo de práticas de silenciamentos pela violência “costurada” no corpo infantil - Schons, Carme Regina (Organon, 2010)
The present work intends to reflect, starting from the theories of text and discourse, on silencing forms produced in the/by the media regarding children´s exploitation. To elucidate what was proposed, we took into account the concept of language as structure and event, developed by Pêcheux (1983), and the reflections of Orlandi (1996) on the concept of silencing - local silencing and constituent silence. Our question was established from our reading of the corpus: what is delivered by the abuse of the word and what is recovered in the restriction of language? In our analysis, we noticed the work of interdiscursive relationships as much as the one of the relationships of historicity involving specific conditions, since it is in the process of enunciation that the subject-victim enters the scene, is introduced in the social setting and, on being spoken about, assumes an institutionally and socially marked place of fragility and of incapacity of defense.